Retrofitting of Cement Plant with Carbon Capture Technology and Emissions Trading Scheme (ETS): An Integrated P-Graph and AHP Approach - Eunice T. Estrella; Chalmer M. Belaro; Michael Angelo B. Promentilla (Chemical Engineering Transactions, 2023)
Cement manufacturing is an energy-intensive industry and is the third largest greenhouse gas (GHG) emitter accounting for 8 % of the world’s total emissions. There are mitigations to limit its carbon footprint through process optimization and using alternatives to fossil-derived fuels. Another technological option to meet the higher carbon dioxide (CO2) reduction target is carbon capture. The post-combustion process is considered the most straightforward and widely studied among carbon capture technologies (CCTs) in advanced stages of development for industrial application. However, the progress of CCTs on an industrial scale has been hindered by low profitability due to the high capital necessary to upscale the technology and retrofit industrial plants. Sales from utilizing the captured CO2 and carbon taxing and trading benefit the application of these technologies. This paper proposes a methodology built from the P-graph and Analytical Hierarchy Process (AHP) to aid in the planning of retrofitting cement plants with post-CCTs in a cap-and-trade environment utilizing an Emissions Trading Scheme (ETS). Three alternative post-combustion technologies were considered, namely monoethanolamine (MEA) absorption technology, chilled ammonia process (CAP), and membrane-assisted liquefaction (MEM). The criteria used to prioritize alternatives are the net CO2 avoided, profitability, and the retrofitability of the technology to an existing plant. The results suggest that CAP is the most profitable based on P-graph calculation. However, MEA is the most optimal network considering the importance of net CO2 avoided and the level of retrofitability. Further sensitivity analysis of the model shows that CAP is the most applicable technology once the profitability score exceeds 0.8341. CAP and MEA will have an equal ranking at a retrofitability score of 0.0632. More than this score, the latter outranked the other two technologies. Finally, MEM surpassed CAP and MEA at a minimum net CO2 avoided score of 0.7079.